Massinger : the critical heritage - Garrett, Martin (Critical heritage series., 1991)
Martin Garrett's comprehensive collection presents and explains the history of the critical reception to Massinger's work from the early seventeenth to the late nineteenth century. The volume includes extensive selections from the writings of Pepys, Goldsmith, Coleridge, Hazlitt, Lamb and Swinburne, as well as briefer comments from Scott, Byron and Keats. Responses to Massinger's plays from writers as diverse as Boswell, Mrs Thrale, Dickens and Elizabeth Barrett Browning are discussed in Martin Garrett's introduction, which also includes an account of the plays' original political and theatric.